The Kitchen as a Social-Spatial Barometer: Deconstructing the Domestic Realm From a Gender Perspective - Amoroso, Serafina; Alcocer, Atxu Amann (UI Scholars Hub, 2025)
Emergent domesticities have generated new forms of urban life that have dissolved the historical duality between the home and the city. Last century's gender revolution in Western societies, together with contemporary technologies, has affected how people organise their daily lives. Everyday time has replaced typological space, blurring the lines between reproductive and productive activities and consequently affecting private and public spaces and how we live together. Pre- modern dwellings consisted of spatial spaces in which a few pieces of furniture were used to carry out everyday activities and were replaced in 18th-century bourgeois culture by spatial devices organised into 'room.' Defined typologically according to modern concepts such as intimacy, domesticity and privacy, as opposed to the public sphere, room has now become a political tool to challenge the status quo. This article focuses on a renewed understanding of the kitchen as the appropriate element to showcase emerging ways of life related to architecture, gender, and the city, which coexist with the prevailing model of capitalism. The text aims to highlight the shift from a model based on relationships of social reproduction to a (counter-)model relying on caring and collective interactions that can contribute to the unfinished process of gender equality and social justice.